МЕТОДИЧЕСКАЯ КОМПЕТЕНТНОСТЬ ПЕДАГОГА: СУЩНОСТЬ И ДИАГНОСТИКА - Джанабаева, А.; Уразова, М.Б. (SCIENCE and SOCIETY, 2023)
Realization of the needs of modern society in the education system is impossible without high-quality training of teachers with methodological competence. The article presents the author’s vision of the teacher’s methodological competence, revealing its content through its structure (methodological awareness, methodical literacy, methodical creativity, and methodical art) and level structure (creative, erudition, literacy, situational and zero levels).